Performance of Broilers Exposed to Used Litter and Fed Diets with Agolin® Poultry, BMD®/Stafac® or No Additive from 0-42 Days - Sims, M.D.; Zweifel, B.; Williams , P.; Hooge, D.M. (International Journal of Poultry Science, 2018)
Background and Objectives: Agolin® Poultry is an encapsulated blend of essential oil compounds. A 42 day trial was conducted with 1,800 broiler chicks using 3 dietary treatments and 20 pens/treatment (30 chicks/pen) to evaluate live performance. Methodology: Chicks received live coccidia vaccine at placement (day 0). Pelleted basal diets (CON) or diets with Agolin® Poultry (200 mg kg–1, 0-14 days and 100 mg kg–1 14-42 days) or BMD® (55 mg kg–1, 0-28 days) and Stafac® (22 mg kg–1, 28-42 days) were fed. Litter was new wood shavings initially and used litter was added on day 4 to provide Eimeria and bacterial pathogens. Daily light: dark cycle was 16:8 h. Litter was sampled at 14, 28 and 42 days for moisture and ammonia (by analyzing for nitrogen, then calculating theoretical ammonia). Oocysts per gram (OPG) feces were counted and foot pad lesion severity scores (0-2) were taken at 42 days. Results: The 28 and 35-day body weights were heavier on Agolin® or antibiotic diets than CON diets. Weight gain from 14-28 or 14-35 days was greater on Agolin® diets than CON with antibiotic diets intermediate. The 0-35 days mortality-adjusted feed conversion ratios (MAFCR) were lower on Agolin® or antibiotic diets than CON diets. Mortality (2.46-3.18%) was unaffected by treatment. Mortality percentage was unaffected by treatment. Litter moisture, OPG in feces and foot pad lesion scores were not different but 28 day litter ammonia tended to be lower on Agolin® diets. Conclusion: The 35-day BW and 0-35 day MAFCR were significantly improved by Agolin® or antibiotic diets compared to CON diets.